Reorganizing government : a functional and dimensional framework - Camacho, Alejandro E.; Glicksman, Robert L. (New York : New York University Press, 2020)
'Reorganizing Government' seeks to transform how policymakers and scholars understand relationships between government institutions, and offers a pioneering model for constructing and assessing government authority.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 11, 2019).
Keywords: Administrative agencies -- United States -- Reorganization; Decentralization in government -- Law and legislation -- United States; Interagency coordination -- United States; Delegated legislation -- United States; Federal government -- United States; Authority; United States -- Politics and government -- 2017-; Politics and Government; Public administration